Трендовые статистики при обработке данных в системах технической диагностики - Mirgorod, V. F.; Ranchenko, G. S. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
Probabilistic characteristics and the conditions for applying the Halda–Abbe criterion to detect trend dependencies in time series data within technical diagnostics systems are analyzed. An assessment is carried out of the influence of sample correlation, deviations of the a priori distribution during preliminary data processing, and the conditions for the correct use of trend statistics.